THE APPLICATION OF PROBLEM POSING MODEL TO IMPROVE CREATIVE THINKING ABILITY IN ELEMENTARY SCHOOL MATHEMATIC LEARNING - Dewi Retno Larasati; Wahyudi Wahyudi; Endang Endarini (Universitas Negeri Makassar, 2019)
Creative thinking ability is one of competencies that has to be possesed by all people includes elementary school students. Learning process in class doesn’t give any chances yet to all students to achive this competency. It is one of the causes of the low learning outcomes. The study aims to determine and describe creative thinking ability with problem posing model. The model that is used in this study is Kurt Lewin research model, where the process of action research occurs in a contiunous circle, includes the stages of planning, action, observation and reflection. The subject of this study is students from five grade in Salatiga Public Elementary School Tingkir Tengah 2 totaling 29 students. The technique of data collection used test technique and observation. The data were analyzed with comparative descriptive analysis or comparing result form each cycle. The result of this study showed that creative thinking ability increased on cycle I, 6,91% was on ‘very creative’ criteria, 28,27% was on ‘creative’ criteria, 17,24% was on ‘creative enough’ criteria, 13,79% was on ‘less creative’ category and 13,79% was on ‘not creative’ criteria. On cycle II increased, 44.82% was on ‘very creative’ criteria, 37,97% was on ‘creative’ criteria, 13,79% was on ‘creative enough’ criteria, 3,46% was on ‘less craetive’ criteria and no one was on ‘not creative’ criteria. This improvement on creative thinking ability can have a positive impact toward learning outcomes on cycle I which was 55,17% and on cycle II increased the completeness of 86,20%. With this result, it can be concluded that problem posing model could improve students’ creative thinking ability, so the suggestion that could be given is that learning process using problem posing model should be developed and can be made as one of alternative models in learning process